2000
DOI: 10.2337/diabetes.49.8.1367
|View full text |Cite
|
Sign up to set email alerts
|

Influence of obesity and type 2 diabetes on gluconeogenesis and glucose output in humans: a quantitative study.

Abstract: The contribution of gluconeogenesis (GNG) to endogenous glucose output (EGO) in type 2 diabetes is controversial. Little information is available on the separate influence of obesity on GNG. We measured percent GNG (by the 2 H 2 O technique) and EGO (by 6,6-[ 2 H]glucose) in 37 type 2 diabetic subjects (9 lean and 28 obese, mean fasting plasma glucose [FPG] 8.3 ± 0.3 mmol/l) and 18 control subjects (6 lean and 12 obese) after a 15-h fast. Percent GNG averaged 47 ± 5% in lean control subjects and was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
217
3
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(232 citation statements)
references
References 49 publications
11
217
3
1
Order By: Relevance
“…This observation is consistent with the results of previous studies that have suggested that elevated glucose production is not a feature of obesity alone (49), although among diabetic subjects, the increased glucose production rate is exaggerated by obesity (50). A recent study, albeit relying on urinary cortisol-to-cortisone metabolite ratios, has suggested that the downregulation of 11HSD1 in the liver with increasing obesity is less pronounced in type 2 diabetic patients (19).…”
Section: Hsd1 In Obesitysupporting
confidence: 82%
“…This observation is consistent with the results of previous studies that have suggested that elevated glucose production is not a feature of obesity alone (49), although among diabetic subjects, the increased glucose production rate is exaggerated by obesity (50). A recent study, albeit relying on urinary cortisol-to-cortisone metabolite ratios, has suggested that the downregulation of 11HSD1 in the liver with increasing obesity is less pronounced in type 2 diabetic patients (19).…”
Section: Hsd1 In Obesitysupporting
confidence: 82%
“…The combined spice at 500 mg/kg body weight was found to be equipotent to glibenclamide in restoring the levels of these markers to normal. The increased serum levels of urea, creatinine and urate in untreated diabetic rats observed in this study could be due to insulin deficiency and the consequent inability of glucose to reach extrahepatic tissues which activate gluconeogenesis as an alternative source of glucose (Gastaldelli et al 2000). Also, because of the increased proteolysis needed to sustain this route, deamination of glucogenic amino acids released into the plasma consequently leads to increased urea in the blood.…”
Section: Indexmentioning
confidence: 88%
“…In humans with type 2 diabetes, there is evidence for enhanced gluconeogenesis and glycogenolysis after an overnight fast, particularly in patients with severe fasting hyperglycaemia [1,22,23,24,25,26,27]. Although liver was insulin resistant in ob/ob mice, this did not result in enhanced hepatic glucose production.…”
Section: Discussionmentioning
confidence: 99%